The effects of cyber harassment and its relationship with coping styles, coping self-efficacy and the actions victims take - Lim, Jia Chang (2014)
This study examined cyber harassment in a Singapore population. Victims of cyber harassment were asked about aspects of their harassment incident. Cyber harassment was also studied in relation to anxiety, coping styles, coping self-efficacy as well as the actions that victims had taken against their harassers. The study included a college age sample as well as public respondents and responses were collected through an online survey. Results revealed 42% of the victims had been harassed by strangers, 72% of the incidents had lasted for less than a month, 42% of victims were harassed on social networking sites, 36% of victims had first encountered their harassers offline and 72% of these harassment incidents were purely online encounters. Results also suggested that a problem-focused coping style, high coping self-efficacy and taking direct actions against the harasser could contribute to lower anxiety levels. On the other hand, an emotion-focused and maladaptive coping style contributed to higher levels of anxiety. Coping self-efficacy was positively correlated with a perceived satisfactory resolution of the harassment incident. While some of these results were non-significant, all correlations were in the hypothesized direction. The results and implications of the study are discussed in relation to the actions and coping styles that victims can take to protect themselves from future psychological impacts.